The Accuracy of Relative Valuation Methods in Predicting the Offer Price of Indonesian IPO Stocks - Ravenza, Rafi; Raden Aswin Rahadi (Journal Integration of Social Studies and Business Development, 2024)
The increasing Initial Public Offerings (IPO) trend in Indonesia has created many investment opportunities for institutional and retail investors. However, multiple valuation methods often result in varying IPO price predictions, leading to uncertainty and confusion among investors. This study aims to assess the effectiveness of relative valuation methods in predicting IPO offer prices, focusing on widely adopted methods due to their simplicity and accessibility. The research evaluates three popular relative valuation metrics: the price-to-book (P/B) ratio, the price-to-earnings (P/E) ratio, and the price-to-sales (P/S) ratio. By analyzing companies that went public in Indonesia in 2023 and utilizing average financial ratios from the preceding year, the study seeks to determine which method provides the most accurate price predictions. The findings indicate that the P/B ratio is the most reliable method, achieving an average absolute error of 51.1%. This suggests that the P/B method minimizes valuation errors more effectively than P/E and P/S ratios. Moreover, regression models' P/B ratio demonstrates the highest adjusted R² value of 0.781, further validating its predictive accuracy. The implications of this study are significant for investors and financial analysts who rely on relative valuation methods to make informed decisions about IPO investments. By highlighting the P/B ratio's superior performance in predicting IPO offer prices, this research contributes to the ongoing discourse on valuation methodologies and their practical application in emerging markets like Indonesia.